(untitled) (Contemporary Mathematics, 2025)
The paper focuses on the incompressible Navier-Stokes equations coupled with the Landau-Lifshitz-Gilbert equations, incorporating the Dzyaloshinskii-Moriya (DM) interaction and a V-flow term, derived as models for magnetovi-scoelastic materials. It is demonstrated that under assumption small initial data there exist the global smooth solutions for this coupled system posed on T2 or R2 .